PERAN ORANG TUA DALAM MENDUKUNG KETERAMPILAN MEMBACA PERMULAAN DI SD NEGERI NONGKOSAWIT 01 WILAYAH PERKOTAAN (URBAN AREA) - Rizqita Herliana, Aisnan; Farizqo Irvan , Moh. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading difficulties experienced by elementary school students can hinder their active participation in learning. This study aims to analyze the role of parents in supporting early reading skills among first-grade students at SDN Nongkosawit 01 in an urban context, as well as to identify factors that support and hinder this process. A qualitative approach was employed, with data collected through observation, interviews, and document analysis. The findings reveal that parental roles as educators and facilitators at home, particularly in urban areas, have not been optimally fulfilled. This is largely influenced by common urban constraints, including parents’ limited time due to work demands, inadequate understanding of effective learning strategies, and the absence of a literacy-rich home environment. The study underscores the need to strengthen parental involvement in urban settings through socialization, mentoring, and practical strategies to support the holistic development of students’ early reading skills.